Traditional versus intensive blood glucose control: long-term target range duration and cardiovascular disease risk and all-cause mortality - a real-world cohort study - Zhang, Jingdi; Li, Liuxin; Luo, Donglei; Huo, Zhenyu; Zhang, Xiaoxue; Xu, Yiran; Jiang, Jingyuan; Liu, Tiantian; Wu, Shouling; Huang, Zhe (Frontiers in Endocrinology, 2024)
Objective: For a long time, the dispute about whether improved glycemic control can bring significant benefits has remained unresolved. We aimed to investigate the association of time spent in different fasting glucose target ranges with cardiovascular risk and all-cause mortality in a population with type 2 diabetes (T2DM).Method: A total of 3460 T2DM patients in the Kailuan cohort were included in this study. The Time in Target Range (TITRE) was calculated as the proportion of time that fasting blood glucose (FBG) was within the usual glycemic control range and the intensive glycemic control range between 2006 and 2016. The Cox proportional hazards regression model analyzed the relationship between TITRE, defined by different glucose ranges, and cardiovascular disease and all-cause mortality.Results: During a median follow-up of 4.23 years, a total of 360 CVDs and 238 deaths were recorded. After correcting for traditional risk factors, we observed that in the conventional blood glucose control group, each increase of 1 standard deviation in TITRE was associated with a 23% (HR, 0.77; 95%CI, 0.68-0.87) reduction in CVD risk and a 20% reduction in all-cause mortality (HR, 0.80; 95%CI, 0.69-0.92). Similar results were also observed in the intensified blood glucose control group. In the conventional blood glucose control group, participants with TITRE of 50% or more had an absolute incidence rate of CVD of 16.77%, whereas in the intensified blood glucose control group, participants with TITRE of 50% or more had an absolute incidence rate of CVD of 11.82%.In patients with type 2 diabetes, achieving near-normal blood glucose levels appears to significantly reduce the risk of diabetes-related cardiovascular outcomes.